Dampak Adiksi Media Sosial terhadap Capaian Akademik: Meta-Analisis 2015-2025 - Abdul Aziz, Nurdin (CV RIFAINSTITUT, 2024)
The phenomenon of social media addiction has emerged as a critical issue demanding scholarly attention within the educational landscape of the 21st century. Amid the accelerating tide of digitalization, social media has evolved beyond a platform for interaction—it has become a cognitive arena that shapes thinking patterns, learning behaviors, and academic outcomes. This study presents a meta-analysis of 82 empirical studies published between 2015 and 2025, aiming to identify overarching patterns, quantitative effects, and moderating variables that influence the relationship between social media addiction and academic achievement. The synthesis reveals a negative correlation of moderate strength (r = -0.32), indicating that higher levels of social media addiction are associated with lower academic performance among students and university learners. However, the effect size varies across cultural contexts, platform types, and individual time-management strategies. Conceptually, these findings reaffirm that social media addiction is not merely a behavioral issue but an epistemic concern that erodes cognitive focus and learning discipline. Therefore, the urgency of digital literacy, reflective learning, and educational policies responsive to media dynamics becomes increasingly vital. This study aspires to contribute a fresh perspective to digital education discourse that is holistic, humanistic, and contextually grounded.